Psychological stress among university students in wartime: A longitudinal study - U. B. Mykhaylyshyn; A. V. Stadnik; Yu. B. Melnyk; J. Vveinhardt; M. S. Oliveira; I. S. Pypenko (International Journal of Science Annals)
Background and Aim of Study: War has an extremely negative effect on people’s psyches. This is especially true for student youth. They have to build personal lives and continue their studies in these difficult and traumatic conditions. The aim of the study: to identify the peculiarities of the dynamics of psychological trauma, and the manifestations of depression, anxiety and stress among students in wartime. Material and Methods: The study involved university students from Ukraine and European Union countries in 2022-2024. Respondents aged 20-50 years were divided into 4 groups. Group 1 consisted of 107 students, including 64 (59.8%) males and 43 (40.2%) females, living in areas where there was no hostilities or shelling (November 2022). Group 2 consisted of 103 students, including 52 (50.5%) males and 51 (49.5%) females, living in the area of active hostilities (November 2022). Group 3 consisted of 112 students, including 41 (36.6%) males and 71 (63.4%) females, living in areas where there was no hostilities or shelling (March 2024). Group 4 consisted of 115 students, including 30 (26.1%) males and 85 (73.9%) females, living in the area of active hostilities (March 2024). The study involved the development of the author’s questionnaire and the adapted psychological test on the DASS-21, which is available on the Google Forms platform. The technique was found to have adequate internal consistency. Cronbach’s alpha was 0.807. Results: Longitudinal studies have shown that university students in wartime are characterised by a tendency to increase psychogenics related to martial law, communication and safety. A closer look at the dynamics of psychopathological symptoms revealed a trend towards increased depression and anxiety, as well as a stabilisation of acute stress indicators in all groups. This indicates a serious deterioration in the mental health of the students and a further chronicisation of their neurotic disorders. Conclusions: The negative impact of the war in Ukraine on the mental health of student youth requires the active implementation of psychological support measures and psychoprophylaxis in accordance with individual psychodiagnostic findings.